Pemikiran Filsafat Islam Mulla Sadra - Nurkhalis Nurkhalis (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Mulla Sadra name the Islamic philosophy the al-Hikmah al-Muta'aliah. According to him, al-hikmah al-muta'aliah is the knowledge which is based on an intellectual intuition (irfani or isyraq dzawq), rational proof ('aql or istidlal), and the shari'ah (burhany). Al-Hikmah al Muta'āliyyah is a synthesis of three mode of thinking, namely: theology with character polemical dialectical (Jaddaly), philosophy with the character of demonstrative (burhany), theosofy with the illuminastic and gnostic character (dhawq). This all elements are derived from the Koran, and Hadith. Human‟s knowledge is divided into two: husuly science and hudhury science. Husuly science (acquired), knowledge gained through ilham (inspiration), al-kasyf (unveiling) and al-hads (intuition). Science hudlury (innate) covers about perception which, according to Mulla Sadra it was identified as an act which refers to the sensation, thus the perception is the designation for the deeds done by any soul to know the object of knowledge, both physical and non physical. He divides perception into four levels; sensory perception (al-Hiss), imajinal (al-khayal), intuition senses (wahm), intelegency (ta'aqqul). Intelegency as the highest level is based upon the degree achievement (tajarud) with the cosmos, while the sensory perception is the lowest level. The term tajarud is actually ascribed to Allah as a Being Payers (wajib al-wujud) who do not have an attachment to anything else but Himself. God‟s knowledge is objective existence (al-wujud al-'ainy). Human‟s knowledge is mental existence (al-wujud alDzihny).